2000
DOI: 10.1021/jp993994s
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscopic Ordering of Polyelectrolyte Chains in Foam Films:  Role of Electrostatic Forces

Abstract: Recent studies using a thin film balance of free-standing thin aqueous films (foam films) containing polyelectrolytes resulted in jump-like discontinuities in the film thickness with increasing outer pressure. These jumps in film thickness correspond to an oscillation of the disjoining pressure. The oscillation period of the disjoining pressure scales as c -0.5 with the polyelectrolyte concentration c. A mesoscopic ordering of the chains in the film similar to that found in aqueous semidilute polyelectrolyte s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 24 publications
(36 reference statements)
7
70
2
Order By: Relevance
“…With increasing ionic strength, the number of visible oscillations and their amplitude decreases, until they disappear at high salt concentrations (around 10 À2 mol l À1 ). 27,65 This is well correlated with SANS experiments, where a characteristic peak disappears above 10 À2 mol l À1 salt. 36 The degree of polymer charge has also a strong impact on the stratication behavior.…”
Section: Effect Of the Polymer Systemsupporting
confidence: 82%
“…With increasing ionic strength, the number of visible oscillations and their amplitude decreases, until they disappear at high salt concentrations (around 10 À2 mol l À1 ). 27,65 This is well correlated with SANS experiments, where a characteristic peak disappears above 10 À2 mol l À1 salt. 36 The degree of polymer charge has also a strong impact on the stratication behavior.…”
Section: Effect Of the Polymer Systemsupporting
confidence: 82%
“…Since the organization of the polyelectrolyte solution is caused by the repulsion between polyelectrolyte chains any variation that will reduce this repulsion, e.g. decreasing the linear charge density of the polyelectrolyte or increasing the ionic strength, will lead to a reduction in the oscillating structural force, which is confirmed by both theory [9] and experiments [62,66]. Simulations have shown that linear polyelectrolytes are aligned preferentially parallel to the confining walls [9], and experiments have shown that the periodicity of the oscillations scale with the bulk concentration to the power of À1/2 [63,67,68], i.e.…”
Section: Polyelectrolytes At Similarly Charged Surfacesmentioning
confidence: 59%
“…Measurements of the disjoining pressure in thin liquid films of PE solutions as a function of film thickness demonstrated an oscillatory pressure [95,239,240,241] with a period of the oscillation of the order of the peak position in the bulk structure factor (which was discussed in Sec. 3.6).…”
Section: Adsorbing Charged Polymersmentioning
confidence: 93%